Asymmetric Suppliers’ Optimal Investment Timing Decisions - Manoj KUMAR (Eurasian Journal of Business and Economics, 2019)
This paper extends Boyle and Guthrie (2003) to investigate the interdependent effects of asymmetric financing capacities and investment costs on investment timing decisions in a duopoly with a first-mover advantage. We demonstrate several novel findings. First, suffering a significant cost disadvantage, the supplier with a larger financing capacity can still be the leader when the risk of future funding shortfalls is relatively high. Second, a weaker supplier with a significant lower financing capacity and a small cost disadvantage can even be the leader under some degree of the risk of future funding shortfalls. In addition, the weaker supplier that is still more liquidity constrained cannot be the leader anymore as its financing capacity improves and closes to that of the rival. Third, only when the risk of future funding shortfalls is relatively low, small asymmetry of investment costs can make the rival’s preemption threat effective. Finally, higher project return volatility can lead to a change of the supplier’s role from a follower to a leader under some degree of the risk of future funding shortfalls, thereby lowering the supplier’s optimal investment trigger